REVIEW OF EDUCATIONAL PHILOSOPHY: A CRITICAL ANALYSIS OF THE IMPLEMENTATION OF PANCASILA PROFILES IN THE SCHOOL CURRICULUM - Anggreni, Ni Luh Putu Yesy; Suastra, I Wayan; Pramanta, Made Deni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This study explores the implementation of the Pancasila Profile in the school curriculum through the perspective of a review of educational philosophy. Pancasila, as the foundation of the Indonesian state, has a central role in shaping the character and morality of the younger generation. The focus of this research is on a critical analysis of how the values of Pancasila are reflected and integrated in the structure of the formal education curriculum. The research method uses a qualitative approach by collecting data through literature analysis, interviews with teachers, and observation of educational practices in selected schools. The context of the implementation of the Pancasila Profile involves an understanding of the way Pancasila values are articulated in curriculum objectives, education policies, and implementation strategies at the national and local levels. The results showed that the implementation of the Pancasila Profile had a significant impact on the formation of student character and the integration of Pancasila values in learning. However, challenges such as resistance to change and inconsistent understanding of Pancasila values were also identified as aspects that needed attention. This research contributes to an in-depth understanding of how educational philosophy plays a key role in shaping the implementation of the Pancasila Profile. These findings provide a basis for recommendations for improvement and development of education policies that are more effective in making Pancasila values a key pillar in formal education. The implications of this research can help direct steps towards a more sustainable education system and in accordance with the spirit of Pancasila as a moral guide for Indonesia's young generation.